2020
DOI: 10.1111/ene.14322
|View full text |Cite
|
Sign up to set email alerts
|

Progressive supranuclear palsy often develops idiopathic normal pressure hydrocephalus‐like magnetic resonance imaging features

Abstract: Background and purpose Idiopathic normal pressure hydrocephalus (iNPH) is a clinical entity without established pathological hallmarks. Previous autopsy studies reported that patients with an antemortem diagnosis of iNPH had a different postmortem diagnosis, commonly progressive supranuclear palsy (PSP). Disproportionately enlarged subarachnoid space hydrocephalus (DESH) has been reported as a characteristic feature of iNPH on magnetic resonance imaging (MRI). In addition, periventricular white matter hyperint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…These indices proved to be useful in distinguishing PSP and iNPH from healthy controls and from other neurodegenerative diseases, but less useful to distinguish PSP and iNPH between each other [9].…”
Section: Introductionmentioning
confidence: 92%
“…These indices proved to be useful in distinguishing PSP and iNPH from healthy controls and from other neurodegenerative diseases, but less useful to distinguish PSP and iNPH between each other [9].…”
Section: Introductionmentioning
confidence: 92%
“… 102 In addition, there is increasing evidence for the importance of comorbidities in patients with iNPH such as Alzheimer’s disease and Parkinson-plus syndrome. 105 106 107 It is therefore important to find biomarkers for diagnosing iNPH as well as for selecting good candidates for surgery.…”
Section: Idiopathic Normal-pressure Hydrocephalusmentioning
confidence: 99%
“…Co-occurrence of idiopathic normal-pressure hydrocephalus-like magnetic resonance imaging features in progressive supranuclear palsy I read with great interest the article by Ohara et al [1], who found that progressive supranuclear palsy (PSP) patients more often develop idiopathic normal-pressure hydrocephalus (iNPH)-like magnetic resonance imaging (MRI) features than those with other neurodegenerative diseases. I congratulate the authors for conducting such an original study; however, I would like to make some comments to help clarify their report and present some crucial perspectives.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Remarkably, Ohara et al report that eight patients with PSP and two with Parkinson's disease (PD) received a CSF tap test based on iNPH-like MRI features [1]. Three out of the eight PSP patients and one PD patient were reported to have responded to the CSF tap test [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation